Pulse electrothermal plasma accelerators and its application in the technologies - Kolyada, Yu.E.; Bizyukov, A.A.; Bulanchuk, O.N.; Fedun, V.I. (Вопросы атомной науки и техники, 2015)
The possibility of the pulsed electrothermal plasma accelerator application was shown for some technological problems. In particularly it was demonstrated the possibility to produce colloidal solutions contained metallic particles, the modification of the structural steel surface properties by means of surface Titanium doping, the construction of pulsed electrothermal plasma accelerator as the borehole generator of the elastic pulses and use it for the intensification of the hydrocarbons production. Показана можливість застосування імпульсного електротермічного плазмового прискорювача для вирішення низки технологічних завдань. Зокрема, розглянуто можливості: одержання колоїдних розчинів, що містять металеві наночастинки; модифікації поверхневих властивостей конструкційної сталі шляхом поверхневого легування титаном; створення на базі імпульсного електротермічного плазмового прискорювача свердловинного генератора пружних імпульсів та його використання для інтенсифікації видобутку вуглеводнів. Показана возможность использования импульсного электротермического плазменного ускорителя для решения ряда технологичных задач. В частности, рассмотрены возможности: получения коллоидных растворов, содержащих металлические наночастицы; модификации поверхностных свойств конструкционных сталей путём поверхностного легирования титаном; создания на основе импульсного электротермического плазменного ускорителя скважинного генератора упругих импульсов и использования его для интенсификации добычи углеводородов.